PENGARUH ANGKA KEMATIAN BAYI, ANGKA PARTISIPASI SEKOLAH, DAN RASIO KETERGANTUNGAN TERHADAP INDEKS PEMBANGUNAN MANUSIA - Novitasari, Ni Made Ayu Widya; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323]DO - 10.24843/EEP.2022.v11.i08.p14, 2022)
This study aimed to analyze the effect of infant mortality, school enrollment rate, and dependency ratio on the Human Development Index in districts/ cities of Bali Province. The data used in this study is secondary data for 6 years in 9 districs/cities Bali Province were obtained from various sources such as CPM and the Bali Provincial Health Department. The analysis technique used is panel data regression.  The study showed that the infant mortality,school enrollment rate, and dependency ratio simultaneously affect the human development index in districts/ cities of Bali Province. Partially, the infant mortality rate and dependency ratio have a significant and negative effect on the human development index in  n districts/ cities, Bali Province, while the school enrollment rate was positive effect but an insignificant effect . keyword : infant mortality rate, school enrollment rate, dependency ratio, human development index